Culture positivity by hospital bath bed modalities: an ecological study - Paulela, Débora Cristina [UNESP]; Mondelli, Alessandro Lia [UNESP]; Mangini Bocchi, Silvia Cristina [UNESP]; de Carvalho Nunes, Hélio Rubens [UNESP] (Acta Paulista de Enfermagem, 2022)
Objective: To verify microbiological culture positivity of hospitalized patients, with a nursing prescription for bed bath, in three disjoint and sequential periods of bed bath modalities: conventional (CBB), disposable (DBB) and disposable plus 2% chlorhexidine degerming (DBB-CX). Methods: This is an ecological, time series study of 48 months, in three periods (P1=CBB; P2=DBB; P3=DBBCX), with secondary data from electronic medical records of patients who were admitted to a hospital in the state of São Paulo, Brazil. Results: In the periods of disposable baths, the percentage of culture positivity was, on average, 14.6% lower when compared to the months in which bed bath was conventional. In the DBB-CX period, the percentage of culture positivity was, on average, 19.3% lower when compared to the CBB period months. However, there is no evidence of difference in the percentage of culture positivity between DBB (b = -14.6%; 95%CI = (-18.9% to -10.3%) and DBB-CX (b = - 19.3%;95%CI = (-24.4% to -14.22%) For each year more in patients’ mean age, the percentage of culture positivity increases by an average of 0.3% (p=0.060). There was no seasonal association for microbiological culture positivity in bath modalities. Conclusion: Microbiological culture positivity in patients with a nursing prescription for bed bath is lower when disposable modalities are used. It is recommended to routinely adopt DBB, leaving the prescription of DBB-CX only for skin degermation for invasive and operative procedures and hand hygiene of health professionals.
Positividad de culturas por modalidades de baño en cama hospitalaria: estudio ecológico
Positividade de culturas por modalidades de banho no leito hospitalar: estudo ecológico
Keywords: Bacterial infections; Baths; Cross infection; immersion; Products for bath